The sitcom reader : America viewed and skewed - Dalton, Mary M., 1962-; Linder, Laura R. (State University of New York Press, 2005)
"Despite the popularity of the sitcom, one of the oldest and most ubiquitous forms of television programming, The Sitcom Reader is the first book to offer critical essays devoted specifically to the form. The contributors address important topics in relation to sitcoms, such as conventions of the form, the family, gender, sexual orientation, ethnicity, work and social class, and ideology, and they do so from a variety of perspectives, including cultural studies, feminist theory, queer theory, and media studies."--Jacket